Avaliação longitudinal da resposta dos anticorpos IgM e IgG contra a Duffy binding protein II (DBPII) do Plasmodium vivax em indivíduos expostos à malária na Amazônia Brasileira. - Camila Maia Pantuzzo Medeiros (2020)
Plasmodium vivax is the most widespread human malaria parasite. This parasite invades reticulocytes via a major pathway that depends on the interaction between the apical protein Duffy Binding Protein II (DBPII) and its cognate receptor on the erythrocyte surface, the Duffy antigen receptor for chemokines (DARC). While DBPII is a leading P. vivax malaria vaccine candidate, the ligand domain is highly polymorphic and induces strain-specific humoral immune response. Recently, we developed a surface-engineered DBPII vaccine candidate, named DEKnull-2, which retains the conserved functional epitopes needed for receptor binding and DBP dimerization. Prof-of-concept studies demonstrated that DEKnull-2 is highly recognized by naturally exposed P. vivax individuals who have broadly neutralizing antibodies able to block DBPII-DARC interaction (BIAbs). Although IgG antibodies have been associated with DBPII protective immunity, the role of IgM antibodies remain largely understudied. Hence, the goal of the current study was to investigate the relationship between IgG and the less studied IgM antibody response against conserved (DEKnull-2) and variable (Sal1, a natural variant circulating in the study area) DBPII epitopes. For this purpose, we serologically evaluated 163 adults with long-term exposure to malaria in a rural community of the Brazilian Amazon (Rio Pardo, AM). The study design included a 9-year retrospective cohort study, with cross-sectional surveys carried out during periods of high (phases I e III) and low malaria transmission (phase II). The conventional antibody response was determined by ELISA assay using DBPII-related recombinant proteins (DEKnull-2 and Sal1), with antibody avidity assessed by using a denaturing agent. The functional antibody response (BIAbs) was determinate through an in vitro functional assay with DBPII-transfected cells. Taken together, the results of this long-term follow-up study showed that (i) IgM antibody response towards DBPII-variant-epitopes (strainspecific Sal1), while IgG antibody response towards the conserved epitopes of the protein (DEknull-2); (ii) IgM variant-specific DBPII antibodies were relatively stable throughout the study, but IgG variant-specific antibodies were poorly sustained at low transmission period; (iii) whereas epitope-conserved IgG antibodies were relatively stable overtime and associated with broadly binding-inhibitory IgG antibodies (BIAbs), IgM antibody response was not associated (positively or negatively) with BIAbs; (iv) peripheral malaria infections (detected by microscopy or PCR-based assay) did not correlate with either IgG or IgM antibody responses; (v) regardless the protein assayed, both antibody responses were related with antibodies of high avidity, with IgG > IgM; (v) finally, the response of IgG did not correlate with IgM response. In conclusion, the long-term IgM response to DBPII appears to be predominantly variant-specific, while the long-term IgG response is directed to the conserved epitopes of DBPII. This was the first follow-up study that investigated the relationship between IgM /IgG antibodies against DBPII, and future studies should explore the contribution of IgM response to malaria-induced immunity.